Pengaruh Etos Kerja dan Kompetensi Terhadap Kinerja Karyawan PT. Surya Segara Safety Marine - Aryani, Diah Ayu; Rini, Hesty Prima (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to ascertain how employees of PT Surya Segara Safety Marine's performance is affected by work ethic and work competence. Quantitative research employing the PLS-SEM (Partial Least Square-Structural Equation Modeling) method is included in this category. Techniques for gathering data through the distribution of questionnaires and documentation 41 PT Surya Segara Safety Marine employees provided responses to this study. The saturated sampling technique was used for the sampling method, and the entire population was used as the research sample in this study. The SMARTPLS 3.0 program was used to calculate the hypothesis testing. This study found that PT Surya Segara Safety Marine employees' performance is significantly and positively influenced by the variables work ethic and employee competence. This means indicating that PT Surya Segara Safety Marine employees will perform better if they have a better work ethic and are more competent. Keywords: Competence; Performance; Work ethic.